Decentralized Decision Authority, Balanced Scorecard and Managerial Satisfaction: PLS-SEM Analysis - Alphun, Cihan; Turker, Nuray; Sainaghi, Ruggero (Academic Conferences and Publishing International Limited, 2023)
Organisations has recently experienced many operational difficulties hence the performance measurement systems (PMSs) have a great deal of importance in understanding organisational effectiveness in the wake of pandemic. Organisations use different types of PMSs according to their specific conditions. This situation is explained by contingency theory that the environmental and/or firm-specific factors cause organisations to use different types of PMSs. One of the organisational factors is the management's structure; particularly decentralised decision authority, is described as the delegation of decision rights throughout the organisation. In this type of an organisational structure, innovative PMS such as the balanced scorecard (BSC) is more effective to meet the information needs of organisations. Numerous studies investigated the relationship between the decentralised decision authority, different PMSs and organisational effectiveness. Nevertheless, researchers emphasise the need for a better understanding of factors influencing the use of innovative PMSs. Furthermore, previous studies only investigated organisational performance but, managerial satisfaction is another outcome of performance measurement implementation and given the received scant attention, it is needed to advance our understanding on this topic. Reviewed literature also indicates the need for more research on the firm's contingent factors, PMS, and managerial satisfaction relationship. In light of methodological developments in PLS-SEM domain, the current study answers this call by conducting research in the hotel industry. Hotel industry is a dynamic industry hence, decentralised decision authority enables to provide effective and timely decisions for arising conditions. Therefore, using the contingency theory, this study proposes and tests a research model which investigates the BSC as a mediator between decentralised decision authority and managerial satisfaction. Data was collected from hotel managers in Turkey and analysed using PLSSEM. The findings demonstrate that decentralised decision authority has a positive effect on the BSC use which gives rise to increase managerial satisfaction. The results thus reveal that decentralised decision authority is related with the managerial satisfaction only through the BSC. This study makes a significant contribution to the largely neglected area in the hospitality performance measurement literature by investigating the aforementioned relationships. It also provides managerial practical implications of the findings. © the authors, 2023. All Rights Reserved.
22nd European Conference on Research Methodology for Business and Management Studies, ECRM 2023 -- 2023-09-06 -- Lisbon -- 198655
Keywords: Balanced Scorecard; Decentralised Decision Authority; Managerial Satisfaction; Performance Measurement System